Rapid Determination of Ochratoxin A in Grape and Its Commodities Based on a Label-Free Impedimetric Aptasensor Constructed by Layer-by-Layer Self-Assembly - Nan, Mina; Bi, Yang; Xue, Huali; Xue, Sulin; Long, Haitao; Pu, Lumei; Fu, Guorui (Toxins, 2019)
A simple and sensitive label-free impedimetric aptasensor for rapid determination of ochratoxin A (OTA) has been developed, which was based on the combination between thiolated aptamer and gold nanoparticles by layer-by-layer self-assembly. Because of the interaction between aptamer and OTA, the relative normalized electron-transfer resistance (ΔRct) values obtained by electrochemical impedance spectroscopy (EIS) was proportional to the concentration of OTA and showed a good linear relationship from 0.1 to 10.0 ng/mL, with a lower detection limit (0.030 ng/mL) than one-step thiolated DNA aptasensor. The established method was successfully applied to detect and analyze OTA in table wine and grape juice, and the recovery was 90.56%–104.21% when PVP effective removed of phenolic substances. The label-free impedimetric aptasensor was used for rapid detection and quantitation of OTA in the inoculated grapes with the Aspergillus Nigri (H1), and the production of OTA (62.4 μg/kg, 20 μg/kg) far exceeded the maximum levels of 2 μg/kg after inoculation for three days. The developed method exhibited a good specificity, high sensitivity, time-efficient, and it could be applied to detect the OTA concentration in grape and its commodities.